Production and Quality Evaluation of Vinegar from Tamarind (Tamarindus indica L.) Fruit Pulp - M. Alawad, Salwa; E. Sulieman, Abdel Moneim; A.Osman, Magdi; A. Mudawi, Hassan (Gezira Journal of Engineering and Applied Sciences; Vol 10 No 1 (2015), 2018)
ABSTRACT       Vinegar is a liquid consisting mainly of acetic acid (CH 3 COOH) and water . The acetic acid is produced by the fermentation of ethanol by acetic acid bacteria . This study aimed to produce vinegar from tamarind fruit pulp and evaluation of its quality. Samples of tamarind fruit were collected from different sites in Sudan: Gedaref (GT), Damazin (DT) and Obeid (OT). The vinegar yields from 1 kg tamarind pulp from (GT), (DT) and (KT) were 300, 200, 260 ml, respectively. The physical characteristics of tamarind fruit pulp and its seeds were determined. The average fruit length, width and weight were 14.28± 0.31mm, 11.06± 1.1mm and 12.33± 0.7g, respectively The production of vinegar was carried out at three stages. The concentration of acetic acid of the produced vinegar from (GT), (DT) and (OT) were equivalent to (16.2%), (19%) and (17.7%), and pH values of these samples were found to be (2.2), (1.9) and (2.0), respectively. The study recommends the efficient industrial use of tamarind fruit in many products such as vinegar.